PEMANFAATAN LINGKUNGAN SEKOLAH MELALUI PENDEKATAN OUTDOOR DALAM PEMBELAJARAN SAINS DI SD - Bambang Gonggo Murcitro (Perspektif Ilmu Pendidikan, 2006)
The objectives of primary education is to give students basic competence to develop their life as an individual, as part of a community and as citizen. On the other hand, the objective of a nature science in primary education is to give students competencies to develop their knowledge, skill, and attitude that is useful in their daily life. Nature science in primary education refers to knowledge rather science. It means that what is teach in primary education are practice things, useful to the living and then in any circumstances and any life aspects. The mission and objectives in teaching nature science in primary education is related to the environment problems in school environment as well as community environment problems in school environment around the students. The environment around the kids should have been used by the teacher to teach natural science because the environment itself the objective, source, and learning facilities. The manufacture of teaching natural science in primary education can be obtained by doing a meaningful learning process.